2016
DOI: 10.1016/s0140-6736(15)00667-4
|View full text |Cite|
|
Sign up to set email alerts
|

Ibrutinib versus temsirolimus in patients with relapsed or refractory mantle-cell lymphoma: an international, randomised, open-label, phase 3 study

Abstract: SummaryBackground Mantle-cell lymphoma is an aggressive B-cell lymphoma with a poor prognosis. Both ibrutinib and temsirolimus have shown single-agent activity in patients with relapsed or refractory mantle-cell lymphoma. We undertook a phase 3 study to assess the effi cacy and safety of ibrutinib versus temsirolimus in relapsed or refractory mantle-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
326
3
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 419 publications
(366 citation statements)
references
References 28 publications
23
326
3
14
Order By: Relevance
“…In randomized trials, ibrutinib is effective as first-line treatment of chronic lymphocytic leukemia (CLL)/ small lymphocytic lymphoma (SLL) (compared with chlorambucil), 1 for relapsed/refractory CLL/SLL (compared with ofatumumab or combined with bendamustine/rituximab), 2,3 or for relapsed/refractory mantle cell lymphoma (compared with temsiroliums), 4 with promising results in the treatment of Waldenström macroglobulinemia. 5 It is anticipated that ibrutinib will become an important part of the therapeutic armamentarium for these conditions.…”
mentioning
confidence: 99%
“…In randomized trials, ibrutinib is effective as first-line treatment of chronic lymphocytic leukemia (CLL)/ small lymphocytic lymphoma (SLL) (compared with chlorambucil), 1 for relapsed/refractory CLL/SLL (compared with ofatumumab or combined with bendamustine/rituximab), 2,3 or for relapsed/refractory mantle cell lymphoma (compared with temsiroliums), 4 with promising results in the treatment of Waldenström macroglobulinemia. 5 It is anticipated that ibrutinib will become an important part of the therapeutic armamentarium for these conditions.…”
mentioning
confidence: 99%
“…Subgroup analyses of a single‐arm phase II trial of ibrutinib in 111 patients with relapsed/refractory MCL found similar ORRs, irrespective of multiple baseline factors, including tumour bulk (≥5 and ≥10 cm cut‐offs), ≥2 prior treatment regimens and refractory disease (less than partial response to last prior therapy) (Wang et al , 2015). More recently, an open‐label phase III study showed that ibrutinib was superior to temsirolimus with regard to improvements in PFS overall and when broken down by subgroups (Dreyling et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent approval of novel therapies, patients with rr mcl generally respond poorly to treatment, with the median os typically being only 1-2 years 11 . Median progression-free survival (pfs) ranges from 3.9 months to 14.6 months, and overall response rates (orrs) range from 22% to 72% depending on the type of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Median progression-free survival (pfs) ranges from 3.9 months to 14.6 months, and overall response rates (orrs) range from 22% to 72% depending on the type of treatment. Although no current standard of care has been established in the rr setting, ibrutinib shows the most promising single-agent efficacy of the currently approved agents, being associated with a median pfs of 13.6-14.6 months and with orrs ranging from 54% to 72% [11][12][13] . In comparison, the reported median pfs was 9.2 months for bortezomib, 3.9-8.7 months for lenalidomide, and 4.8-6.2 months for temsirolimus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation